A Perspective on Human Rights, The Economic Liberalization of Education Provision in Indonesia - Pratama, Obi (Entita: Jurnal Pendidikan Ilmu Pengetahuan Sosial dan Ilmu-Ilmu Sosial, 2023)
A single embedded case study and a descriptive qualitative methodology are used in this study. sources of information include people or organizations, activities or events, documents and archives, as well as literature. The objectives of this study are to identify the economic liberalization that has taken place in the implementation of education in Indonesia, identify the effects of this economic liberalization, and discover the economic liberalization that has taken place in the education provision in Indonesia through its perspective of human rights. Education is a fundamental right that every citizen has access to, as stated in the preamble of the Undang-Undang Dasar 1945, which is about the nation’s intellectual life. Everyone needs education to provide them with new knowledge. The economic liberalization of education provision refers to the recent use of education as a new tool to profit from all angles. Those with lower income levels may notice the effects of economic liberalization in the implementation of this education because it becomes more challenging for them to obtain the best education. Complete facilities and top-notch teaching staff are necessary for good education. The results of the study indicate that diverse parties must promote instruction that adheres to Indonesian national standards. Disparities and prejudice against particular groups seeking a great education must be removed in order to guarantee that every student has equitable access to a high-quality education that will help them develop their potential and talents in the future. The government, as the highest authority, should carry out planned programs in line with the desired objectives by evaluating field data and keeping an eye on connected parties’ performance. The government will be able to maintain broad control over program execution as a result, without concentrating on or supporting any particular group.